Experimental investigation of tri-reforming on a stationary, recuperative TCR-reformer applied to an oxy-fuel combustion of natural gas, using a Ni-catalyst. (1st December 2020) - Wachter, Philipp; Gaber, Christian; Demuth, Martin; Hochenauer, Christoph
Abstract: Experimental investigations into stationary thermochemical recuperation are presented with three modifications compared to current researches: (I) A recuperative reformer was used. Current waste heat regeneration concepts use regenerative heat exchangers, which have numerous disadvantages: size, leakage and unsteady operation. In contrast, recuperative reformers enable the possibility of compact design and allow stationary operation. (II) The energy available for the reforming process was provided with the thermal energy of exhaust gases. (III) Oxygen was added to the reforming reaction. In the experiments, exhaust gases were used as reactants. The reactants are thus characterized by a fixed molar ratio of H 2 O / CO 2 = 2 / 1 causing a maximum steam-to-carbon-ratio of 0.5. Steam-to-carbon-ratios of this size favour coke formation. The addition of oxygen to the reactants caused partial oxidation of methane which additionally released steam and increased the reaction temperature. Coke formation was thus inhibited. The influence of oxygen on the CH 4 -conversion and on the formation of carbon was determined. A maximum CH 4 -conversion-rate of 89.85% was achieved by adding oxygen without the formation of carbon deposits. Moreover, temperature measurements inside the reactor were performed. The addition of oxygen influenced the reaction temperature due to partial oxidation of methane resulting in a temperature increase of more than 100 ∘ C . Highlights: Tri-reforming on a stationary operated, recuperative reformer was performed. Exhaust gases were used as the heat source for tri-reforming. The influence of oxygen on coke formation during tri-reforming was determined. The addition of oxygen resulted in a carbon free operational mode. Temperature distribution measurements of the reactor were executed.